Preparation and magnetic properties of Cu0.4Zn0.6Cr0.5Sm0.06Fe1.44O4/ polyaniline nanocomposites - 李良超 仇海珍 王育萍 蒋静 徐烽 (Journal of rare earths, 2008)
A self-propagating combustion synthesis （SPCS） method, citrate SPCS method, was used to synthesize Cu0.4Zn0.6Cr0.5SmxFe1.5-xO4 （x=-0-0.1） nanosized powders at relatively low temperature. Polyaniline/Cu0.4Zn0.6Cr0.5Sm0.06Fe1.44O4 （CZCS0.06FO） nanocomposites were prepared by in situ polymerization of aniline in the presence of CZCS0.06FO ferrites. The structures, morphologies, and ferromagnetic properties of ferrite powders and nanocomposites were characterized by powder X-ray diffractometer （XRD）, transmission electron microscope （TEM）, scanning electron microscope （SEM）, and vibrating sample magnetometer （VSM）. The results indicated that ferrite powders were coated effectively by polyaniline, which reduced the agglomeration of ferrite particles to certain extent, and was helpful to the decentralization and stabilization of nanoparticles. The nanocomposites with core-shell structure under applied field exhibited hysteresis loops of the ferromagnetic nature. The nanocomposites were fit for being used as soft magnetic material because of their lower coercivity than that of pure ferrites.